2013
DOI: 10.14260/jemds/388
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Fluorosis- An Epidimio-Clinico-Radiological Study

Abstract: Skeletal fluorosis is endemic problem in many parts of world including India as well as West Bengal effecting mainly low socio-economic group of populations. This study is to detect the epidemiological and clinical as well as radiological survey to detect and help to prevent the morbidity and mortality of the people from the so called slow environmental poison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Fifty-three eligible studies were uncovered . Twenty-six studies seemed to be eligible at preliminary review, but were deemed ineligible for the following reasons: association of MSD with HBD not assessed (n = 9) [86][87][88][89][90][91][92][93][94], HBD details not provided (n = 1) [95], HBD not assessed (n = 7) [96][97][98][99][100][101][102], independent impact of HBD could not be concluded (n = 1) [103], not indoor environment (n = 4) [104][105][106][107], not MSD (n = 3) [108][109][110], and not original research (n = 1) [111]. Sixteen studies [34,38,[47][48][49][50]58,63,67,69,70,72,73,75,78,79] uncovered in the current review were also reported in our other systematic review on HBDs and spine-related MSDs (back pain, neck pain) [13].…”
Section: Study Selectionmentioning
confidence: 99%
“…Fifty-three eligible studies were uncovered . Twenty-six studies seemed to be eligible at preliminary review, but were deemed ineligible for the following reasons: association of MSD with HBD not assessed (n = 9) [86][87][88][89][90][91][92][93][94], HBD details not provided (n = 1) [95], HBD not assessed (n = 7) [96][97][98][99][100][101][102], independent impact of HBD could not be concluded (n = 1) [103], not indoor environment (n = 4) [104][105][106][107], not MSD (n = 3) [108][109][110], and not original research (n = 1) [111]. Sixteen studies [34,38,[47][48][49][50]58,63,67,69,70,72,73,75,78,79] uncovered in the current review were also reported in our other systematic review on HBDs and spine-related MSDs (back pain, neck pain) [13].…”
Section: Study Selectionmentioning
confidence: 99%